Discursive authority in COVID-19 vaccination fact-checking: the case of @butantanoficial on Instagram: the case of @butantanoficial on Instagram - Oliveira, Augusto Vinicius de; Alexandre, Gabriel Guimarães; Komesu, Fabiana; Assis, Juliana Alves; Fluckiger, Cédric (Revista do GEL, 2024)
From the theoretical-methodological perspective of New Literacy Studies and French Discourse Analysis, this paper aims to investigate discursive strategies employed by Butantan Institute in publications aimed at debunking dis- or misinformation about COVID-19 vaccination in Brazil. The corpus consists of 32 visual-verbal textual productions (posts) published by the @butantanoficial profile on the digital social network Instagram in the years 2020, 2021, 2022, and 2023. The hypothesis, grounded in the studies of Amossy (2022), is that over these years, the Institute has made various attempts to establish authority in the discourse surrounding COVID-19 vaccination, particularly concerning the possession of what would be perceived as “true statements” about vaccination, in contrast to “false statements”, within a context of disinformation and fake news. The results highlight the prioritization of strategies in the discursive construction and re-elaboration of an ethos closely tied to different demands from the public as well as to interests of the Institute itself, across various stages of the COVID-19 pandemic.